Search for resonant production of second-generation sleptons with same-sign dimuon events in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2019)
A search is presented for resonant production of second-generation sleptons ((mu) over tilde (L),(nu) over tilde (mu)) via the R-parityviolating coupling. gimel'(211) to quarks, in events with two samesign muons and at least two jets in the final state. The smuon ( muon sneutrino) is expected to decay into amuon and a neutralino (chargino), which will then decay into a second muon and at least two jets. The analysis is based on the 2016 data set of proton- proton collisions at root s = 13 TeV recorded with the CMS detector at the LHC, corresponding to an integrated luminosity of 35.9 fb(-1). No significant deviation is observed with respect to standard model expectations. Upper limits on cross sections, ranging from 0.24 to 730 fb, are derived in the context of two simplified models representing the dominant signal contributions leading to a same- sign muon pair. The cross section limits are translated into coupling limits for a modified constrained minimal supersymmetric model with. gimel'(211) as the only nonzero R-parity violating coupling. The results significantly extend restrictions of the parameter space compared with previous searches for similar models.
Keywords: LEPTON-NUMBER; SUPERSYMMETRY; MODEL; BARYON; CONSERVATION; EXTENSION; VIOLATION; INVARIANT; SPHENO; TOOL